A Phenomenological Investigation of Creative Teaching in Counselor Education. (7th June 2019) - McGhee, Carla; Baltrinic, Eric R.; Laux, John; Clark, Madeline; Liu, Yanhong; Harmening, Debra
Abstract : The authors conducted a phenomenological investigation of creative teaching with 10 counselor educators. The resulting 4 themes suggest creative teaching (a) is shaped by past experiences, (b) promotes student engagement, (c) is not formulary, and (d) requires risk taking. Implications for creative teaching strategies and training are provided. Limitations and implications for future research on creative pedagogy are discussed.